Halo moon : [large type] a Jared Delaney western - Jones, Jim, 1950- (Jones, Jim, 1950- Jared Delaney western., 2023)
"As Jared Delaney rides home from a cattle drive to Colorado, he is haunted by a nightmare of menace and impending change, signified by the moon encircled by a hazy band of light . . . a halo moon. When he arrives in Cimarrón, he is shocked to discover that his friend and mentor, Sheriff Nathan Averill, has been murdered. Against his wifes wishes, he agrees to seek vigilante justice to avenge Nathans death. Estranged from his family and friends, Jared travels the perilous trail to vengeance, unaware that a truly evil man is stalking him and his family at the same time. Refusing to accept the counsel of those close to him, he finds moral guidance from an unlikely source-a young man with a checkered past on the run from the law. Will the end justify the means? How many people will die along the way?"--"--